Creating electronic educational resources for students of technical higher education institutions using SharePoint Designer - Mamuta, M. (Problems of Engineer-Pedagogical Education, 2020)
The article addresses the problem and advisability of creating electronic educational resources for students in higher education. The author proves in his article that the quality training of students is not possible without the use of electronic educational resources. In the course of training, the teacher must not only give knowledge, but also teach future specialists to learn, and find sources of additional knowledge independently. This calls for a new model of education based on modern information technologies, which not only facilitates access to information but also reinforces the educational system. The author argues that electronic learning has some didactic advantages over paper-based learning. The electronic educational resource has a hypertext structure and is more convenient to use in the educational process, since the use of hypertext makes it possible to overcome the limitations inherent in text teaching materials. Information retrieval and assimilation are greatly facilitated, resulting in an efficient understanding of the content of particular materials. In this connection, the possibility of providing university students with electronic educational resources created in the Microsoft Office SharePoint Designer environment was explored. For this purpose, the training manual «Metrological Measurements» created in the Microsoft Office Word environment was used. The author describes in detail how to do the preparatory work in the Word environment. A description of the creation of an e-learning resource in the Microsoft Office SharePoint Designer environment is accompanied by the necessary images and explanations. In the article, the author describes only one of the options for providing institutions of higher education with electronic educational resources and plans to further explore the means of creating electronic educational resources.